Peran Bahasa dan Inovasi Teknologi Bahasa dalam Transformasi Digital - Nurleli Hairani Harahap; Erna Ikawati (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
This study is motivated by the importance of language as humanity’s primary means of communication one that not only conveys information but also shapes ways of thinking, culture, and social understanding as well as the growing development of language technology innovations alongside the advancement of digitalization in Indonesia. The objective of this study is to comprehensively examine the concept of language, as well as the development and implementation of language technology in supporting digital transformation across various sectors. The method used is a qualitative descriptive approach involving a literature review through the analysis of journals, books, and related scientific sources, which are then analyzed using content analysis and source triangulation techniques to ensure data accuracy. The research findings indicate that language technologies, such as natural language processing, speech recognition, and machine translation, have experienced rapid development since 2020 and have made significant contributions in the fields of education, industry, and public services, although they still face challenges such as corpus limitations and linguistic diversity. In conclusion, language plays a fundamental role in human life and is supported by language technologies capable of enhancing efficiency, improving access to information, and driving digital transformation; therefore, sustained research support and cross-sector collaboration are necessary to ensure its development remains optimal and relevant to societal needs.